Clinical and Ultrasonographic Features of Distal Ulnar Neuropathy: A Review - Karvelas, Kristopher R.; Walker, Francis O. (Frontiers in Neurology, 2019)
Focal ulnar neuropathy at the wrist is a rare but problematic disorder often associated with the unique anatomy of this nerve as it courses through Guyon’s canal, a superficial fibro-osseous tunnel in the proximal ulnar palm. The electrophysiologic features of this disorder have been well characterized, but the sonographic anatomy of the nerve across the wrist and palm has yet to be systematically described in normal and abnormal states. In this review, we describe the basic anatomy and the sonographic appearance of the nerve in the wrist and palm in normals and individuals with pathology. The value of using US in conjunction with electrodiagnostic testing is emphasized as the two tests together provide critical information regarding etiology, predisposing factors, and functional significance. Furthermore, ultrasound is useful as a patient educational tool to promote behavioural changes that assist in nerve recovery when pathology is related to repetitive stress.